Dose response comparison of Nipah virus strains Malaysia and Bangladesh in hamsters exposed by the intranasal or intraperitoneal route. - Sara C Johnston; Ju Qiu; Sarah L W Norris; Rekha Panchal; Elizabeth M Punger; Melissa Teague; Joshua L Moore; David N Dyer; Ondraya M Frick; Stephen C Stevens; Jimmy Fiallos; Harold L Mills; et al. (PLoS ONE)
Nipah virus, a zoonotic pathogen, can cause debilitating disease and death in humans. Currently, countermeasures are limited, with several in various stages of testing but none yet FDA-approved for human use. Evaluation of countermeasure candidates requires safety testing in humans, as well as efficacy testing against lethal challenge in animal models. Herein, we describe the characterization and comparison of the intraperitoneal and intranasal Syrian golden hamster models for Nipah virus strains Malaysia and Bangladesh. Overall, the intraperitoneal route of exposure resulted in a more consistent lethal outcome, regardless of virus strain. Therefore, the IP model was subsequently used to evaluate the use of Favipiravir as a potential positive control for future studies investigating NiV countermeasures. In contrast to prior reported results regarding Favipiravir in Nipah virus-infected hamsters, Favipiravir was only fifty percent effective at preventing death following lethal challenge, regardless of Nipah virus strain. The data suggest that Favipiravir is only partially protective against Nipah virus in hamsters, and, thus, would likely not be an ideal candidate as a positive control in future efficacy studies.